(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Fine art classes are considered as one of the main subjects in the educational process of auxiliary schools. Because visual arts classes serve to enrich children’s artistic and aesthetic outlook. Under the influence of visual arts, children’s level of emotional awareness increases, and their intellectual and willful qualities develop. Correction of hand motor skills is also performed effectively.